(untitled) (International journal of artificial intelligence, 2026)
This article examines the effectiveness of using information technologies in teaching quantities to primary school students. The study focuses on the pedagogical significance of digital tools, multimedia resources, and interactive technologies in developing students’ understanding of quantities, measurement concepts, and numerical relationships. Modern information technologies enhance learners’ cognitive activity, increase motivation, and support the formation of logical thinking and practical skills. The research analyzes methodological approaches to integrating information technologies into the teaching process and highlights their role in improving the quality and efficiency of mathematics education in primary grades. The findings demonstrate that the purposeful use of information technologies contributes to better learning outcomes and helps students master quantitative concepts more effectively.